1981
DOI: 10.1073/pnas.78.1.626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the immunogenically active components of the Sm and RNP antigens.

Abstract: The spectrum of cellular targets in the autoimmune diseases is both large and varied and includes among the nuclear components the so-called Sm and RNP antigens associated with systemic lupus erythematosus. The use of immunoaffinity chromatography with dual specificity for the Sm and RNP antigens has allowed for their substantial purification from rabbit thymus in parallel and in quantity. In lieu of a functional assay, the use of a counterimmunoelectrophoresis assay provided a sensitive and rapid means ofmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…Thus, the Sm core proteins were synthesized and appeared to be available for association with the RNAs in VSV-infected cells; however, their assembly with the RNAs was inhibited. Because only a subset of the proteins precipitated by anti-Sm serum are antigenic (1,13,27,37,39), the data presented in Fig. 7 and 8 show that in VSV-infected cells, the anti-Sm-reactive core proteins appeared to form a complex in the absence of U RNAs, as shown previously with HeLa cells (6,7).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Thus, the Sm core proteins were synthesized and appeared to be available for association with the RNAs in VSV-infected cells; however, their assembly with the RNAs was inhibited. Because only a subset of the proteins precipitated by anti-Sm serum are antigenic (1,13,27,37,39), the data presented in Fig. 7 and 8 show that in VSV-infected cells, the anti-Sm-reactive core proteins appeared to form a complex in the absence of U RNAs, as shown previously with HeLa cells (6,7).…”
Section: Resultssupporting
confidence: 51%
“…The small nuclear ribonucleoproteins (snRNPs) that are immunoprecipitable by the lupus Sm autoantibody specificity have been implicated in the processing of mRNA (14, 26). The snRNPs contain the snRNAs (Ul, U2, U4, U5, and U6) which are also thought to be products of RNA pol II and require trimethyl 5' capping, methylation, and excision of extraneous sequences (1,5,18,27,28,35,37). Previous work has suggested that the snRNAs are synthesized in the nucleus as precursors that are transported to the cytoplasm where they are processed to their mature sizes, assembled into RNPs, and then transported back to the nucleus (5, 6, 34, 42).…”
mentioning
confidence: 99%
“…In general, this has been accomplished by comparing the titers of antibody reactive with untreated (Sm plus RNP) and RNase-treated (Sm) antigens, as in the hemagglutination assay (2). However, the existence of other RNasesensitive or resistant antigens in nuclear extracts (18), as well as the observation that Sm may be partially sensitive (19,20) and RNP partly resistant (21) to RNase, make a more direct approach desirable. For this reason, we have attempted to distinguish between anti-Sm and anti-RNP antibodies using methods that are independent of the RNase sensitivity or resistance of the antigens to estimate more accurately the relative amounts of these antibodies in SLE and MCTD sera.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the Ul snRNP consists of the U I small RNA and at least nine associated polypeptides (3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Three of these proteins, known as 68K (Mr = 68,000 D),2 A (Mr = 33,000 D), and C (Mr = 22,000 D) are unique to the U1 snRNP.…”
Section: Introductionmentioning
confidence: 99%